Kampung Tenun Kota Samarinda: Studi Pendidikan Masyarakat untuk memberdayakan masyarakat melalui Pariwisata Berbasis Kearifan Lokal - Sari, Syifa Aprita; Mustangin, Mustangin; Lukmanul, A. Ismail (LPPM Universitas Ibn Khaldun, Bogor, 2024)
This study aims to analyze the process of community empowerment in weaving tourism village communities. The research approach in this study is a qualitative approach because it is in accordance with the purpose of this study, which is to examine in depth how the process of community empowerment carried out in the development of weaving village tourism. Data collection in this study used data collection techniques, namely interviews with informants, namely village governments, weaving village managers, and people living in weaving villages. In addition, it uses observation techniques and document studies. Data analysis in this study uses data analysis techniques, namely data reduction, data presentation, and conclusions. The results showed that the empowerment process analyzed used the awareness stage, namely by identifying community needs through joint discussions with the weaving village community. The results of the discussion showed that the people of weaving village have less anxiety about existence. So that a weaving village was formed as a tourist village. In addition, there are stages of community education in the form of providing tourism management training so that people have skills in tourism management. Keywords: Community Empowerment, Community Education, Tourism Village